THE PROFILE OF HIV INFECTED PREGNANT WOMAN IN TERTIARY HOSPITAL - Khalisha, Mujahidah; Akbar, M. Ilham Aldika; Lestari, Pudji (Lux Mensana: Journal of Scientific Health, 2022)
Introduction. In Indonesia, HIV infection is one of the main health problems. Mother or baby with HIV / AIDS have a great opportunity to contribute in maternal and infant mortality. Besides, maternal and infant mortality rates determine the public health quality of a country. This research was conducted based on the negative impact caused by HIV infection and the lack of data on infected pregnant HIV women in Surabaya. This research also expected to find out the main challenges in providing care services, both in terms of health and HIV education for health workers. Method. This research was a descriptive retrospective study to find out the characteristics of HIV infected pregnant women in Regional Public Hospital Dr. Soetomo Surabaya from January-December 2019. There were 36 HIV pregnant women included as a research subject. Results & Analysis. This study shows that the characteristics of HIV infected pregnant women who gave birth in Regional Public Hospital Dr. Soetomo Surabaya has the majority aged of 31-35 years (33.3%), who working as private employees (44.4%), with the latest education is high school (55.6%), married (97.2%), and multigravida (80.6%). Regarding their HIV, most patients (55.6%) had taken ARV for more than 6 months without viral load results (63,8%), and gave birth by C-section (88, 8%). Discussion. Early diagnosis and follow-up of therapy implemented by HIV infected pregnant women and their babies is important to reduce the mother-to-child transmission rate.